Isolation and characterization of yeast for the production of rice wine with low fusel alcohol content. - Huawei Yuan (Public Library of Science (PLoS), 2021)
Fusel alcohols (FAs) are a type of flavor compound found in rice wine. An overly high FA content not only leads to spicy, bitter, and astringent taste but also has side effects. Therefore, screening for yeast that produce low FA contents has attracted much attention. Thirty-two yeast strains were isolated from fermenting material during Luzhou-flavor liquor production in this study. Strain YB-12 was selected as a suitable candidate for rice wine production. The strain was identified as a member of the genus Meyerozyma based on phylogenetic analysis using 26S rDNA gene sequences. The ability of strain YB-12 to produce ethanol was similar to that of Saccharomyces cerevisiae NRRL Y-567, while isobutanol and isoamyl alcohol production was only 53.96% and 50.23%, respectively, of that of NRRL Y-567. The FA yield of rice wine produced with strain YB-12 was reduced to 51.85% in a 20 L fermenter. These results demonstrate that strain YB-12 presents promising characteristics for use in the production of rice wine with a potentially low content of FAs.